A method for preparing layered double hydroxide polyacrylamide nanocomposite hydrogel

By adding anti-deposition additives to the polyacrylamide hydrogel and adjusting the temperature to improve the stability of the layered double hydroxide sol and directly crosslinking with acrylamide, nanocomposite hydrogels with ultra-high mechanical properties are prepared, which solves the problem of the existing hydrogels being easily broken in high-pressure formations, significantly improving the mechanical properties and scope of application.

CN117624429BActive Publication Date: 2025-04-18ANHUI TIANRUN CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311693795.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Existing polyacrylamide hydrogels are prone to breakage in high-pressure formations, and cannot seal the high-pressure wellbore and cannot meet the requirements of underbalanced drilling for gel strength.

Method used

By adding anti-deposition additives and adjusting the system temperature, the stability of the layered dihydroxide sol is improved and directly crosslinked with acrylamide to prepare a layered dihydroxide polyacrylamide nanocomposite hydrogel with ultra-high mechanical properties.

Benefits of technology

The tensile strength, compression stress, elastic modulus, toughness and adhesion of the hydrogel are significantly enhanced, meeting the requirements for gel strength of underbalanced drilling, while reducing the need for toxic organic solvents and reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117624429B_ABST
    Figure CN117624429B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of high molecular polymers for oil fields, and provides a method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel. First, cobalt nitrate, aluminum nitrate and urea are mixed, and a cobalt aluminum layered double hydroxide sol is synthesized in situ after heating. A red laser is used to irradiate to produce a Tyndall effect, and the system temperature is lowered. An anti-settling aid is added before the bright "pathway" in the cobalt aluminum layered double hydroxide sol disappears to obtain a stable cobalt aluminum layered double hydroxide sol; the cobalt aluminum layered double hydroxide sol is then added to acrylamide as a crosslinking agent, stirred, and an initiator is added after an inert gas is introduced, and polymerized under an inert atmosphere to obtain a polymer hydrogel; and finally, post-treatment is performed to obtain a layered double hydroxide polyacrylamide nanocomposite hydrogel. The invention improves preparation efficiency, saves reagents, and reduces preparation costs; the obtained product has enhanced performance, which is conducive to application in underbalanced drilling of oil and gas fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of high molecular polymers for oil fields, in particular to a method for preparing layered double hydroxide polyacrylamide nanocomposite hydrogel. Background Art

[0002] In recent years, hydrogels formed by polyacrylamide and its derivatives have been widely used in the fields of drug release, enzyme reaction control, biodegradable materials, oil and gas field development, etc., especially in the underbalanced drilling process of oil and gas fields, that is, the freezing valve technology of polyacrylamide gel, which has attracted wide attention due to its advantages such as low operating cost and no pollution to oil and gas formations. However, for high-pressure formations, conventional polyacrylamide hydrogels used as freezing valves are easily broken due to their own low mechanical strength and low toughness, and cannot achieve sealing of high-pressure wellbores, and cannot meet the gel strength requirements of underbalanced drilling. Therefore, such defects limit the application scope of polyacrylamide hydrogels.

[0003] To this end, researchers have conducted in-depth research and proposed a variety of strategies to improve the mechanical strength of hydrogels. Currently, nanocomposite hydrogels, double network structure hydrogels and topological structure hydrogels have been reported. Among them, nanocomposite hydrogels are a successful and simple strategy. Its basic principle is to realize the compounding of polymers and nanomaterials on the molecular scale through reasonable structural design, so that the material has both the rigidity of nanomaterials and the flexibility of polymers, thereby achieving the improvement of mechanical properties. Layered double hydroxides have been used to prepare nanocomposite hydrogels with ultra-high mechanical properties because of their advantages of ultra-large specific area and rich adsorption active sites. For example, the prior art CN106317322B discloses "a nanocomposite gel, its preparation method and use", and specifically discloses that acrylate and nitrate-type layered double hydroxides are added to a stripping solvent, dispersed, and then separated to obtain a colloidal substance; then the colloidal substance and acrylamide are added to the stripping solvent, and a copolymerization reaction is carried out after oxygen removal to obtain a nanocomposite gel. For example, the patent number CN106543324A is "An organic / inorganic nanocomposite luminescent hydrogel based on layered hydroxide and its preparation method", and specifically discloses that a layered rare earth hydroxide is synthesized by a one-step coprecipitation method, and then it is stripped and dispersed in a glycine solution, and acrylamide monomer is added for in-situ free radical polymerization, and a nanocomposite hydrogel with excellent luminescent properties is successfully prepared. It can be seen from this that in the process of preparing nanocomposite gels in the prior art, a stripping solvent (formamide or glycine) needs to be added for dispersion, and the polymerization process is also carried out in the stripping solvent. This is mainly because the layered double metal hydroxide is unstable in the water system and will be rearranged into a three-dimensional structure, resulting in poor polymerization effect with acrylamide monomer. The use of a stripping solvent can overcome the above problems; however, the dispersion of the layered double metal hydroxide and the polymerization of the layered double metal hydroxide and acrylamide monomer both need to be carried out in a stripping solvent, so a large amount of stripping solvent needs to be added, which will increase the cost of preparation, and the stripping solvent is generally an organic liquid, which has certain toxicity and is environmentally unfriendly.

[0004] Therefore, based on the prior art, the present invention improves the preparation method of layered double hydroxide polyacrylamide nanocomposite hydrogel, improves the stability of layered double hydroxide sol by combining adding an anti-settling aid and adjusting the system temperature, so that the freshly prepared layered double hydroxide sol is directly cross-linked with acrylamide to obtain layered double hydroxide polyacrylamide nanocomposite hydrogel with ultra-high mechanical properties. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel with simple preparation method, cost saving and strong mechanical properties, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel comprises the following steps:

[0008] Step S1: Cobalt nitrate, aluminum nitrate and urea are mixed, and the temperature is raised to T1 to synthesize a cobalt aluminum layered double hydroxide sol in situ. During the process, red laser irradiation is used to produce a Tyndall effect to form a bright "pathway", and the system temperature is lowered to T2. Before the bright "pathway" in the cobalt aluminum layered double hydroxide sol disappears, an anti-settling aid is added to obtain a stable cobalt aluminum layered double hydroxide sol;

[0009] Step S2: adding the stable cobalt aluminum layered double hydroxide sol prepared in step S1 as a crosslinking agent to acrylamide, stirring to mix evenly, introducing an inert gas for 30-50 minutes, then adding an initiator, polymerizing under an inert atmosphere for 5-7 hours to obtain a polymer hydrogel;

[0010] Step S3: post-treating the polymer hydrogel obtained in step S2 to obtain a layered double hydroxide polyacrylamide nanocomposite hydrogel.

[0011] Preferably, the mass ratio of the cobalt nitrate, aluminum nitrate, urea and anti-settling aid in step S1 is (10-30): (10-30): (1-10): (0.2-1.0).

[0012] Preferably, the anti-settling aid is polyamide wax and / or fumed silica.

[0013] Preferably, in step S1, the temperature T1 is 90-100°C, and the temperature T2 is 0-10°C.

[0014] Preferably, the mass ratio of acrylamide to cobalt aluminum layered double hydroxide sol and initiator in step S2 is 1:(0.001-0.01):(0.01-0.015).

[0015] Preferably, the initiator is a mixture of ammonium persulfate and sodium bisulfite, and the weight ratio of the ammonium persulfate to the sodium bisulfite is (1-2):1.

[0016] Preferably, the inert gas in step S2 is nitrogen, the purity of the nitrogen is ≥ 99.99%, and the flow rate of the nitrogen is 60-70 m / s. 3 / h.

[0017] Preferably, the post-processing in step S3 includes the process of drying, crushing and screening after cutting.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention creatively prepares a stable cobalt aluminum layered double hydroxide (Co / Al-LDH) sol by adding a small amount of anti-settling aid and lowering the system temperature. In the case that the Co / Al-LDH nanosheets do not aggregate, the freshly prepared Co / Al-LDH is used as a cross-linking agent to directly cross-link with acrylamide, so that the hydroxyl groups on the Co / Al-LDH nanosheets coordinate with the amide groups on the acrylamide, and the interaction of hydrogen bonds is combined to prepare the cobalt aluminum layered double hydroxide polyacrylamide nanocomposite (Co / Al-LDH / PAM NC) hydrogel by in situ polymerization, avoiding the use of toxic organic solvents or modifiers to strip and disperse the Co / Al-LDH, which not only reduces the stripping or dispersion process, but also helps to speed up the preparation process and improve the preparation efficiency, and reduces the use of stripping solvents, is environmentally friendly, and reduces the preparation cost.

[0020] (2) The present invention creatively polymerizes the improved and stabilized Co / Al-LDH with acrylamide (PAM) to prepare Co / Al-LDH / PAM NC hydrogel, which significantly enhances its tensile strength, compressive stress, elastic modulus, toughness and adhesion, thereby expanding the application range of the Co / Al-LDH / PAM NC hydrogel, especially meeting the requirements of underbalanced drilling on the strength of the polyacrylamide gel valve. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a schematic diagram of the process of preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] See also Figure 1 , the present invention provides:

[0024] Embodiment 1

[0025] A method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel comprises the following steps:

[0026] Step S101: Cobalt nitrate, aluminum nitrate and urea are mixed, and the temperature is raised to 90°C to synthesize a cobalt aluminum layered double hydroxide sol in situ. During the process, red laser irradiation is used to produce the Tyndall effect to form a bright "pathway", and the system temperature is lowered to 0°C. Before the bright "pathway" in the cobalt aluminum layered double hydroxide sol disappears, an anti-settling aid (polyamide wax) is added to obtain a stable cobalt aluminum layered double hydroxide sol. The mass ratio of cobalt nitrate, aluminum nitrate, urea and anti-settling aid is 10:10:1:0.2.

[0027] Step S102: The stable cobalt aluminum layered double hydroxide sol prepared in step S101 is added to acrylamide as a crosslinking agent, stirred to mix evenly, and an inert gas (nitrogen with a purity of ≧99.99% and a flow rate of 60 m / s) is introduced. 3 / h) for 30 minutes, then add the initiator, polymerize for 5 hours under an inert atmosphere to obtain a polymer hydrogel. The mass ratio of acrylamide to cobalt aluminum layered double hydroxide sol and the initiator is 1:0.001:0.01, the initiator is a mixture of ammonium persulfate and sodium bisulfite, and the weight ratio of ammonium persulfate to sodium bisulfite is 1:1.

[0028] Step S103: Cut the polymer hydrogel obtained in step S102 into pieces, dry, crush and sieve (this is a conventional process and will not be described again here), so as to obtain a layered double hydroxide polyacrylamide nanocomposite hydrogel. Specific embodiment 2

[0030] A method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel comprises the following steps:

[0031] Step S201: Cobalt nitrate, aluminum nitrate and urea are mixed, and the temperature is raised to 100°C to synthesize a cobalt aluminum layered double hydroxide sol in situ. During the process, red laser irradiation is used to produce the Tyndall effect to form a bright "pathway", and the system temperature is lowered to 10°C. Before the bright "pathway" in the cobalt aluminum layered double hydroxide sol disappears, an anti-precipitation aid (fumed silica) is added to obtain a stable cobalt aluminum layered double hydroxide sol. The mass ratio of cobalt nitrate, aluminum nitrate, urea and anti-precipitation aid is 30:30:10:1.0.

[0032] Step S202: The stable cobalt aluminum layered double hydroxide sol prepared in step S201 is added to acrylamide as a crosslinking agent, stirred to mix evenly, and an inert gas (nitrogen with a purity of ≧99.99% and a flow rate of 70 m / s) is introduced. 3 / h) for 50 min, then add the initiator, polymerize for 7 h under an inert atmosphere to obtain a polymer hydrogel. The mass ratio of acrylamide to cobalt aluminum layered double hydroxide sol and the initiator is 1:0.01:0.015, the initiator is a mixture of ammonium persulfate and sodium bisulfite, and the weight ratio of ammonium persulfate to sodium bisulfite is 2:1.

[0033] Step S203: Cut the polymer hydrogel obtained in step S202 into pieces, dry, crush and sieve (this is a conventional process and will not be described again here), so as to obtain a layered double hydroxide polyacrylamide nanocomposite hydrogel. Specific embodiment 3

[0035] A method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel comprises the following steps:

[0036] Step S301: Cobalt nitrate, aluminum nitrate and urea are mixed, and the temperature is raised to 95°C to synthesize a cobalt aluminum layered double hydroxide sol in situ. During the process, red laser irradiation is used to produce the Tyndall effect to form a bright "pathway", and the system temperature is lowered to 3°C. Before the bright "pathway" in the cobalt aluminum layered double hydroxide sol disappears, an anti-settling aid (polyamide wax and fumed silica) is added to obtain a stable cobalt aluminum layered double hydroxide sol. The mass ratio of cobalt nitrate, aluminum nitrate, urea and anti-settling aid is 15:25:6:0.6.

[0037] Step S302: The stable cobalt aluminum layered double hydroxide sol prepared in step S301 is added to acrylamide as a crosslinking agent, stirred to mix evenly, and an inert gas (nitrogen with a purity of ≧99.99% and a flow rate of 65 m / s) is introduced. 3 / h) for 40 min, then add the initiator, polymerize for 6 h under an inert atmosphere to obtain a polymer hydrogel. The mass ratio of acrylamide to cobalt aluminum layered double hydroxide sol and the initiator is 1:0.006:0.012, the initiator is a mixture of ammonium persulfate and sodium bisulfite, and the weight ratio of ammonium persulfate to sodium bisulfite is 2:1.

[0038] Step S303: Cut the polymer hydrogel obtained in step S302 into pieces, dry, crush and sieve (this is a conventional process and will not be described again here), so as to obtain a layered double hydroxide polyacrylamide nanocomposite hydrogel.

[0039] Performance characterization: The performance of the layered double hydroxide polyacrylamide nanocomposite hydrogels obtained in specific examples 1-3 was characterized, and the results are shown in Table 1 (including the control group: the Co / Al-LDH content was 0).

[0040] Table 1 Performance test results of layered double hydroxide polyacrylamide nanocomposite hydrogels obtained in specific examples 1-3

[0041]

[0042]

[0043] From the above data, it can be seen that the tensile stress, compressive stress, elastic modulus, toughness and adhesion of the Co / Al-LDH / PAM NC prepared by the present invention are significantly improved, wherein the tensile stress can reach up to 2036mN, the compressive stress can reach up to 860KPa, the elastic modulus can reach up to 3840Pa, and the toughness can reach up to 2.3MJ / m 3 , the highest adhesion force reaches 8700mN. This is because the layered double hydroxide has a layered structure, and combining it with polyacrylamide can significantly improve the mechanical properties of polyacrylamide. The present invention also adds polyamide wax and / or fumed silica as an anti-precipitation aid, which not only prevents the coagulation of Co / Al-LDH, but also increases the probability of combining Co / Al-LDH with PAM, promotes the combination of the two, and thus further improves the mechanical strength of the nanocomposite hydrogel. In addition, the addition of polyamide wax and / or fumed silica can also increase the viscosity of the system.

[0044] Analysis shows that the present invention prepares a stable Co / Al-LDH sol by adding an anti-settling aid and adjusting the system temperature: first, the anti-settling aid includes polyamide wax and / or fumed silica, wherein the polyamide wax forms a strong network structure in the sol system to prevent the sol particles from settling, and the polyamide wax also has the characteristics of strong strength and good heat resistance, and is particularly suitable for high molecular chemical polymers used in oil fields; fumed silica is an aggregate containing multiple hydroxyl groups on the surface, and the addition of fumed silica can prevent the neutralization of the electrolyte solution and the Co / Al-LDH solution caused by the heterogeneous charged colloid particles. The fumed silica can easily form a uniform three-dimensional network structure in the liquid system due to the combination of hydrogen bonds, further reducing the sedimentation of Co / Al-LDH sol particles, overcoming the problem in the prior art that "layered double hydroxides are unstable in water systems and will be rearranged into a three-dimensional structure, resulting in poor polymerization with acrylamide monomers". In addition, when fumed silica is not subjected to shear force, its three-dimensional structure will be restored, the viscosity will increase, and it has good thixotropic properties. Combined with its own hardness, heat resistance and high chemical stability, it is very suitable for use in high molecular chemical polymers for oil fields. Secondly, the temperature of the system is reduced during the preparation of cobalt aluminum layered double hydroxide sol, which is beneficial to reduce the probability of collision and combination of colloidal particles, and can also improve the stability of the sol to a certain extent. Therefore, the prepared composite hydrogel has a denser network structure, better mechanical strength and better adhesion to the well wall, and can be used for underbalanced drilling in oil and gas fields.

[0045] In summary, the present invention realizes the use of freshly prepared Co / Al-LDH as a cross-linking agent to directly cross-link with acrylamide without aggregation of Co / Al-LDH nanosheets, so that the hydroxyl groups on the Co / Al-LDH nanosheets are coordinated with the amide groups on the acrylamide, combined with the interaction of hydrogen bonds, thereby in situ polymerization to prepare the cobalt aluminum layered double hydroxide polyacrylamide nanocomposite hydrogel, avoiding the use of toxic organic solvents or modifiers to strip and disperse Co / Al-LDH, not only reducing the stripping or dispersion process, which is conducive to speeding up the preparation process and improving the preparation efficiency, but also reducing the use of stripping solvents, being environmentally friendly and reducing the preparation cost. The present invention can also avoid adding intermediate substances to bridge the layered double hydroxide and acrylamide (such as patent CN106317322B), and directly cross-linking and polymerizing the amphoteric metal salt of the inorganic acid with acrylamide, further saving the preparation cost.

[0046] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a layered double hydroxide polyacrylamide nanocomposite hydrogel, characterized in that: The following steps are involved: Step S1: mixing cobalt nitrate, aluminum nitrate and urea, raising the temperature to T1 to synthesize a cobalt aluminum layered double hydroxide sol in situ, using red laser irradiation to produce a Tyndall effect to form a bright "pathway", lowering the system temperature to T2, adding an anti-settling aid before the bright "pathway" in the cobalt aluminum layered double hydroxide sol disappears, and preparing a stable cobalt aluminum layered double hydroxide sol, wherein the anti-settling aid is polyamide wax and / or fumed silica, the temperature T1 is 90-100° C., and the temperature T2 is 0-10° C.; Step S2: adding the stable cobalt aluminum layered double hydroxide sol prepared in step S1 as a crosslinking agent to acrylamide, stirring to mix evenly, introducing an inert gas for 30-50 minutes, then adding an initiator, polymerizing under an inert atmosphere for 5-7 hours to obtain a polymer hydrogel; Step S3: post-treating the polymer hydrogel obtained in step S2 to obtain a layered double hydroxide polyacrylamide nanocomposite hydrogel.

2. The method for preparing the layered double hydroxide polyacrylamide nanocomposite hydrogel according to claim 1, characterized in that: The mass ratio of cobalt nitrate, aluminum nitrate, urea and anti-settling aid in step S1 is (10-30): (10-30): (1-10): (0.2-1.0).

3. The method for preparing layered double hydroxide polyacrylamide nanocomposite hydrogel according to claim 1, characterized in that: In step S2, the mass ratio of acrylamide to cobalt aluminum layered double hydroxide sol and initiator is 1:(0.001-0.01):(0.01-0.015).

4. The method for preparing layered double hydroxide polyacrylamide nanocomposite hydrogel according to claim 1, characterized in that: The initiator is a mixture of ammonium persulfate and sodium bisulfite, and the weight ratio of the ammonium persulfate to the sodium bisulfite is (1-2):

1.

5. The method for preparing layered double hydroxide polyacrylamide nanocomposite hydrogel according to claim 1, characterized in that: In step S2, the inert gas is nitrogen, the purity of the nitrogen is ≥ 99.99%, and the flow rate of the nitrogen is 60-70m / s. 3 / h.

6. The method for preparing layered double hydroxide polyacrylamide nanocomposite hydrogel according to claim 1, characterized in that: The post-processing in step S3 includes the processes of drying, crushing and screening after cutting.

Citation Information

Patent Citations

  • A kind of nanocomposite gel, its preparation method and application

    CN106317322B

  • Organic / inorganic nano composite luminescent hydrogel based on layered hydroxide and preparation method thereof

    CN106543324A

  • Gel polish, LED gel polish and LED nail polish

    CN102766399A